1998
DOI: 10.1007/s002340050692
|View full text |Cite
|
Sign up to set email alerts
|

Is local intra-arterial fibrinolysis contraindicated in elderly patients with cerebral artery occlusion?

Abstract: Local intra-arterial fibrinolysis (LIF) is an effective treatment for selected patients in acute thromboembolic occlusion of the middle cerebral artery, vertebrobasilar system or ophthalmic artery. However, the risk/benefit ratio of thrombolysis in patient subgroups requires classification. Advanced age has been regarded as a prognostic factor for poor clinical outcome. We report our experience with LIF in seven patients with a mean age of 79 years (range 76-83 years) who represented thromboembolic occlusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…According to this classification, occlusions were designated as grade 0, lesions allowing contrast material penetration with minimal perfusion were designated as grade I, lesions displaying partial recanalization following thrombolysis were classified as grade II, and those displaying complete recanalization were classified as grade III (6,7). In fact, concerns regarding the risk-to-benefit ratio of intracranial thrombolysis have been raised in many reports in the literature (11,(15)(16)(17)(18)(19)(20)(21)(22), and the only multicenter randomized study that unequivocally demonstrated significant benefit of intravenous thrombolysis was the NINDS rt-PA study, and this study demonstrated benefit only during the first 3 hours following symptom onset (1). Furthermore, the follow-up randomized double-blind placebo-controlled multicenter study, the Second European-Australasian Acute Stroke Study (5), in which intravenous alteplase was evaluated, failed to demonstrate any statistically significant benefit of thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to this classification, occlusions were designated as grade 0, lesions allowing contrast material penetration with minimal perfusion were designated as grade I, lesions displaying partial recanalization following thrombolysis were classified as grade II, and those displaying complete recanalization were classified as grade III (6,7). In fact, concerns regarding the risk-to-benefit ratio of intracranial thrombolysis have been raised in many reports in the literature (11,(15)(16)(17)(18)(19)(20)(21)(22), and the only multicenter randomized study that unequivocally demonstrated significant benefit of intravenous thrombolysis was the NINDS rt-PA study, and this study demonstrated benefit only during the first 3 hours following symptom onset (1). Furthermore, the follow-up randomized double-blind placebo-controlled multicenter study, the Second European-Australasian Acute Stroke Study (5), in which intravenous alteplase was evaluated, failed to demonstrate any statistically significant benefit of thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Die Lysebehandlungen wurden unter Vollheparinisierung durchgeführt und innerhalb von 2 h nach Lysebeginn abgeschlossen. Zunächst wurde Urokinase, später auch rtPA erfolgreich als Fibrinolytikum verwendet [43,44].…”
Section: Introductionunclassified